Family-Centered Prevention Ameliorates the Longitudinal Association of Poverty with Hippocampal and Amygdalar Volumes in Adulthood - Brody, Gene H. (JAMA Pediatr, 2017)
IMPORTANCE: This study provides the first data showing that rural African Americans' participation, during childhood at age 11, in a preventive intervention designed to enhance supportive parenting ameliorates the association of poverty with hippocampal and amygdalar volumes during adulthood at age 25. OBJECTIVE: To determine whether participation in an efficacious prevention program designed to enhance supportive parenting for rural African American children will ameliorate the association between living in poverty and reduced hippocampal and amygdalar volumes that are evident at age 25. DESIGN, SETTING, AND PARTICIPANTS: In the rural southeastern United States, African American parents and their 11-year-old children were assigned randomly to the Strong African American Families (SAAF) program or to a control condition. Parents provided data used to calculate income-to-needs ratios when children were 11 to 13 and 16 to 18 years of age. When the children were 25 years of age, hippocampal and amygdalar volumes were measured using magnetic resonance imaging. EXPOSURE: Household poverty was measured by income-to-needs ratios. MAIN OUTCOMES AND MEASURES: Young adults' whole hippocampal, dentate gyrus and CA3 hippocampal subfields, and amygdalar volumes were assessed using magnetic resonance imaging. RESULTS: Years lived in poverty across ages 11 to 18 years forecast diminished left dentate gyrus and CA3 hippocampal subfields and left amygdalar volumes among young adults in the control condition but not among those who participated in SAAF. CONCLUSIONS AND RELEVANCE: Studies suggest that supportive parenting may offset risks to brain development posed by exposure to poverty during childhood and adolescence. Prior to this study, it was less clear whether these findings reflected a causal process. In this study, we described how participation in a randomized, controlled trial designed to enhance supportive parenting ameliorated the association of years lived in poverty with left dentate gyrus and CA3 hippocampal subfields and left amygdalar volumes. These findings are consistent with a causal role for supportive parenting and suggest a strategy for narrowing social disparities.